Histo-Morphogical Study of Full- Term Placenta in Selected Normotensive And Pre-eclamptic Women in Bangladesh - Khan , Nahid Ahmed; Nahid, Nuzaira; Choudhury, Melia (Journal of Dhaka Medical College, 2023)
Pre–Eclampsia is a disorder in 2nd half of pregnancy, characterized by a combination of hypertension, proteinuria, and edema, secondary to decreased placental perfusion. Clinical studies suggest histo-morphological changes in the placenta of pre-eclamptic women compared to normotensive pregnant women. This study aimed to compare the histo- morphological changes of the placenta in selected pre-eclamptic and normotensive pregnant women. Methods: Two hundred twenty pregnant women were selected with inclusion and exclusion criteria from 3 different medical colleges and divided into two groups. A study group comprised 110 pre-eclamptic women, and a control group comprised 110 normotensive pregnant women. After delivery, tissue samples were collected from the placenta and prepared for histopathological studies by hematoxylin and eosin stain. The mean number of areas of syncytial knot formation, the mean number of areas of cytotrophoblast cell proliferation, the mean number of areas of fibrinoid necrosis, and the mean number of areas of hyalinized villi of pre-eclamptic and normal pregnant women were evaluated. We evaluated the morphology by weight, diameters, number of cotyledons, and placental infarcts. Results: The mean number of areas of syncytial knot formation, cytotrophoblastic cell proliferation, fibrinoid necrosis, and hyalinised villi were significantly higher in the study group compared to the control group. The mean weights, diameters, and the number of cotyledons were considerably lower in the study group compared to the control group. Moreover, the number of infarcted areas was significantly higher in the placentas of pre-eclamptic women. Conclusion: There are histomorphologic changes in the placenta of pre-eclamptic women. J Dhaka Med Coll. 2022; 31(1) : 37-45